The Work of Animals: A Challenge for Social Sciences - Porcher, Jocelyne (Humanimalia, 2014)
In the intellectual landscape concerned with domestic animals, social scientists are rarely to be seen. Yet work, one of the historical objects of social sciences, is at the heart of relations between humans and animals. This article will put forward approaches to studying animal work through the psychology of work and through critical social sciences.